Perencanaan Penanggulangan Kecelakaan Kerja Di CV. Sinar Brahma Rasyid - Chandrahadinata, Dody; Taptajani, Dedi Sa'dudin; Fahrezi, Rio Rizki (Institut Teknologi Garut, 2025)
The rapid development of development programs in Indonesia, including in the industrial sector, has brought both positive and negative effects. One of the negative effects is environmental pollution, workplace accidents, and occupational diseases, which are caused by an imbalance between progress and the level of awareness regarding occupational safety and health. To ensure comfort and safety in the workplace, a strong work culture is essential. Various methods and tools are used to improve business quality and productivity. One of the most common approaches is the hierarchy of controls, which includes elimination, substitution, engineering controls, administrative controls, and the use of personal protective equipment (PPE).The leather industry company CV. Sinar Brahma Rasyid in Garut faces several occupational safety issues. A total of 33 workplace accidents occurred in 2021, 44 in 2022, and 59 in 2023. In response to these issues, the Job Safety Analysis (JSA) method and the hierarchy of controls were used to identify potential hazards and risks, followed by the implementation of control measures.The aim of this study is to identify the factors contributing to workplace accidents, assess risks, and provide recommendations for improvement in the production department of CV. Sinar Brahma Rasyid. The research findings indicate several causes of workplace accidents, such as employees not using PPE, carelessness, disorganized factory layout, and a lack of tools to assist in material handling.The risk assessment categorized the risks into two levels: low and medium. One example of a medium risk is a workplace accident that can result in serious injury. To reduce workplace accidents and occupational diseases, the study recommends ergonomic chair design, the addition of transport equipment, the use of hazard signs, machine operation training, and the implementation of PPE usage.